Carbon Dots Prepared by One-step Sintering Method and their Application for pH Detection - Wang, Yang; Pan, Ruikun; Cheng, Jiaji; Zhang, Lei; Dong, Xiumei (Current Nanoscience, 2025)
IntroductionIn recent years carbon dots (CDs) have attracted researchers due to their unique physicochemical and fluorescent (FL) features, which can be applied in many fields such as battery materials, fluorescence sensing, display, biological imaging and photocatalysis.MethodsWe prepared CDs by using a facile one-step sintering method. The fluorescent properties and the application of pH detection were measured and analyzed.ResultsThe results show that CDs emit bright purplish-blue light centred at 425 nm excited by 355 nm UV light. FL intensity shows a linear relationship with pH values at 1 4 and 7 11, respectively. The reasonable mechanism of the tested effective pH sensitivity is discussed.ConclusionOur study shows that the CDs prepared by the one-step sintering method have great potential to be used as pH sensors for physiochemical measurements.
Keywords: pH detection